POLUTAN LOGAM BERAT DALAM EKOSISTEM MANGROVE - Lestari Lestari (Pusat Penelitian Oseanografi LIPI, 2018)
HEAVY METAL POLLUTANTS IN MANGROVE ECOSYSTEM. Mangrove is an unique tropical ecosystem with the marine, riverine, terrestrial and atmosphericcomponents influencing the occurrence, speciation, bioavailability and fate of trace chemicals. Mangrove ecosystem are one of the most threatened tropical environment due to habitat loss, aquaculture expansion, overharvesting and increase of pollution load. In this paper, the role of mangrove to act as a sink of pollutants, accumulation and biomagnifications of heavy metals is discussed.